High-dose etoposide and cyclophosphamide in adults and children with primary refractory and multiply relapsed acute leukaemias: The Royal Marsden experience. (October 2019) - Carceller, Fernando; Hirsch, Steffen G.; Khabra, Komel; Petterson, Toni; Malik, Rubina; Guerra-García, Pilar; Moreno, Lucas; Marshall, Lynley V.; Taj, Mary; Atra, Ayad; Ethell, Mark; Potter, Mike; et al.
Highlights: Allo-stem cell transplant is the only cure for refractory/relapsed acute leukaemias. Current salvage regimens do not always achieve adequate remission before transplant. High-dose etoposide/cyclophosphamide can salvage some of those patients. Particularly cases with Acute Myeloid Leukaemia and no access to clinical trials. Abstract: Introduction: For patients with primary refractory and relapsed acute leukaemias allogeneic stem cell transplantation is the only hope for cure, but morphological remission is not always achieved after standard salvage regimens. Here we review the experience with high-dose etoposide and cyclophosphamide (HD-Et/Cy) in relapsed/refractory acute leukaemias at the Royal Marsden Hospital. Patients and Methods: Twenty-three patients (15 adults, 8 children) with refractory/relapsed acute myeloblastic (n = 18; 78%), lymphoblastic (n = 4; 17%) or biphenotypic (n = 1; 4%) leukaemia who had failed to respond to at least one previous line of chemotherapy received HD-Et/Cy at our institution between 2006 and 2015. Results: Overall response rate was 21.7% (95%CI 4.0–40.0). Median overall survival was 14.8 months (95%CI 9.1–49.1). Eight (35%) patients (7 AML, 1 biphenotypic leukaemia) proceeded to allogeneic transplant after one cycle of HD-Et/Cy: four of them (50%; 3 adults, 1 child) in complete remission and another four children (50%) with aplastic bone marrow with scattered blasts. Among the transplant recipients, three with AML (38%), ie. one adult (responder) and two children with aplastic bone marrow with scattered blasts, became long-term survivors 9.8, 4.4 and 2.5 years post-HD-Et/Cy, respectively. Toxicity profile was comparable to similar regimens with no treatment-related deaths. The most common grade 3–4 toxicity was febrile neutropenia (96%). Conclusions: HD-Et/Cy can salvage patients with refractory/relapsed AML who remain candidates for allogeneic stem cell transplantation after failure of standard salvage regimens and do not have access to clinical trials.